REABILITATION OF ETHICS THROUGH THE PRISM OF INDIVIDUAL BIOGRAPHY (A. MACINTYRE, H. ARENDT) - Shcherbakova, Anastasiya O. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
The purpose of the article is to study ethical problematics in the philosophical works of Alasdair MacIntyre and Hannah Arendt. On the one hand we have the analysis of virtues ethics and of its place in modern society (through the prism of emotivism ethics inherent to this society), and on the other hand, we have the analysis of action and judgment as scopes of person’s self-representation, which are valuable by themselves. MacIntyre developed his hypothesis about an individual biography pointing out that modern emotivism ethics does not leave a room for conscious ethical worldview, reduces the scope of ethical choice to the very statement of individual preference. By that, a sequence of ethical decisions and preferences in a person’s life acquires irrational and wayward nature, due to which conscious transition from one narrative to another becomes impossible. In its turn, the possibility of individual biography as a holistic story that everyone can tell about themselves provides such an informative nature of ethical views, which have features of a narrative that can be rationally told and rationally perceived by others. Hannah Arendt analyzed the issue of modern ethical crisis from the other side – she studied the ethical dimension of judging ability and the role of action in social interaction. An action (as Arendt believed) becomes the strictly human scope of human activity, in which personality can “open up” (unlike the areas of work and creation). Judging ability appears in this context as a foundation, thanks to which a person becomes able to act: ethical worldview exists in terms of evaluation of something that exists in relation to something due. An action in this context is an active embodiment of a certain worldview position that “unfolds” itself precisely in the area of ethics while being involved in interpersonal interaction. Arendt claimed that an action, due to its nature, is unpredictable and that every human being, who dares to take it, risks getting, in the end, a result that is far from their intentions. Exactly because of it, an action exists in the actor’s biography and the fabrics of interpersonal connections simultaneously – it is the latter, which gives the space for interpretation of an actor’s actions significance. Thus, the individual biography becomes the thing that makes sense only through the prism of interpersonal interaction and mutual interpretations of individual stories.